Pengaruh Moral Reasoning, Budaya Collectivisme, dan Ethical Environment terhadap Tindakan Whistleblowing - Mahwiyah Mahwiyah; Fidiana Fidiana; Wahidahwati Wahidahwati (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to analyze the effect of moral reasoning, collectivist culture, and ethical environment on whistleblowing action. Furthermore, the research applies quantitatively with a questionnaire as the instrument. Measurement and testing of correlation between the research hypothesis variables using the SEM method which will be calculated using the Smart PLS program. The population consists of employees at Syariah Indonesia Bank, Surabaya branch. Moreover, the result shows that moral reasoning has a positive and significant effect on whistleblowing action for employees at Syariah Indonesia Bank, Surabaya branch. Likewise, collectivist culture has a positive and significant effect on whistleblowing action employees at Syariah Indonesia Bank, Surabaya branch. However, an interesting finding concludes that collectivist culture tends to prioritize group needs compared to individuals. Thus, it can affect individual courage to report unethical behavior. In addition, the findings can be a guide for Indonesia Syariah Bank giving insights into creating a culture that supports integrity and transparency. Also, it supports the individual to be brave in reporting ethical violence.